The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0034-75902008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Um Modelo Fuzzy Comportamental para análise de sobre-reação e sub-reação no mercado de ações brasileiro

Abstract: Neste artigo, são apresentados testes empíricos para a investigação de ocorrência de fenômenos de sobre-reação e sub-reação no mercado de ações brasileiro. Para esses testes, é proposto um modelo baseado na teoria de conjuntos Fuzzy, que possui forte relação com as heurísticas de representatividade e ancoramento, estabelecidas na teoria de finanças comportamentais. O modelo proposto é empregado para a formação de carteiras e utiliza indicadores financeiros de companhias abertas. Para as análises são utilizados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
3
0
4
Order By: Relevance
“…268-287, março/abril, 2019 www.anpad.org.br/rac indicadores como o índice P/L. Esse índice mede a qualidade do preço da ação das empresas (Kimura, 2003;Aguiar et al, 2008). Os resultados não confirmaram as suspeitas levantadas (ISF: coef.…”
Section: Análise Dos Resultadosunclassified
See 1 more Smart Citation
“…268-287, março/abril, 2019 www.anpad.org.br/rac indicadores como o índice P/L. Esse índice mede a qualidade do preço da ação das empresas (Kimura, 2003;Aguiar et al, 2008). Os resultados não confirmaram as suspeitas levantadas (ISF: coef.…”
Section: Análise Dos Resultadosunclassified
“…Considerando a proxy utilizada para mensurar o ECO, o índice P/L poderia motivo plausível para o CEO adquirir ações da própria empresa. Ao comparar o resultado da ponderação de diversas empresas, é possível obter argumentos consistentes para escolher um investimento (Aguiar, Sales, & Sousa, 2008;Kimura, 2003), pois este demonstra em quantos anos haveria recuperação o dinheiro investido.…”
Section: Variável De Controle -íNdice P/l (Ipl)unclassified
“…Within this context, Aguiar et al (2008) carried out empirical tests to investigate the occurrence of overreaction and underreaction phenomena in the Brazilian stock market, using a model based on fuzzy set theory, which is closely related with behavioral finance theory, applied to financial indicators from two sets of shares: one from the oil and gas sector and the other from the textile sector, related to the period from 1994 to 2005. The results indicated that the market has informational inefficiencies, given that there is significant evidence of overreaction and underreaction, thus being inconsistent with the EMH.…”
Section: Misvaluation and Behavioral Biasmentioning
confidence: 99%
“…However, despite the evidence of share misvaluation caused by behavioral bias (Aguiar et al, 2008;Dourado & Tabak, 2014), Pimentel (2015) indicates other specific factors of the Brazilian capital market, such as market concentration, high interest rates, and high volatility, which can interfere in the share pricing dynamic and in the returns forecasting models.…”
Section: Misvaluation and Behavioral Biasmentioning
confidence: 99%
See 1 more Smart Citation